Outage Performance of Two Way Full-Duplex Relay Networks with Antenna Selection - Fidan, Efendi; Kucur, Oğuz (IEEE, 2017)
A novel transceiver antenna selection (TRAS) strategy selecting a pair of antennas for transmission and reception at terminal sources for full-duplex (FD) amplify-forward (AF) multi-input multi-output (MIMO) two way relay networks is offered and analyzed. Antenna pair is selected in accordance with maximum and second maximum signal to self-interference-plus-noise ratio (SINR) between the sources and the relay. The exact expression for sum outage probability over Rayleigh fading channels is derived and validated via Monte Carlo simulation technique. Results show that error floor due to a specific self-interference (SI) value is independent from total number of antennas at the sources and begins at the same SINR value for different total number of antennas at the sources. It is also shown that error floor due to SIs can be decreased and performance can be significantly improved by usage of offered TRAS strategy at terminal sources.
Advances in Wireless and Optical Communications (RTUWO) Conference -- NOV 02-03, 2017 -- Riga, LATVIA
Keywords: Transceiver Antenna Selection; Transmit Antenna Selection; Receive Antenna Selection; Full Duplex; Half Duplex; Two Way Relaying Networks; Multi-Input Multi-Output; Rayleigh Fading; Amplify-and-Forward